Stomatal analysis of citrus somatic hybrids obtained by protoplast fusion - Costa, Maria Angélica Pereira de Carvalho; de Almeida, Weliton Antonio Bastos; Mourão Filho, Francisco de Assis Alves; Mendes, Beatriz Madalena Januzzi; Rodriguez, Adriana Pinheiro Martinelli (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to evaluate leaf epidermis morphological characteristics of three citrus somatic hybrids, compared to their parents. Parental and somatic hybrid young leaves were collected and processed for scanning electron microscope observations. Citrus polyploid hybrids have fewer stomata per area and these are larger compared to their diploid parental parents. No differences in internal arrangement of the stomatal cells were detected between parental plants and somatic hybrids. Additional studies may determine if these differences will influence physiological behavior of the plants in the field.
Keywords: stoma; somatic hybridization; scanning electron microscopy; polyploidy